Optimization of up-flow velocity and feed flow rate in up-flow anaerobic sludge blanket fixed-film reactor on bio-hydrogen production from palm oil mill effluent. (1st March 2023) - Akhbari, Azam; Ibrahim, Shaliza; Ahmad, Muhammad Shakeel
Abstract: The present study aims to optimize key operational parameters of the up-flow anaerobic sludge blanket fixed-film (UASFF) reactor using response surface methodology (RSM). A central composite design (CCD) has been applied to accomplish thirteen experimental runs given two main variables, namely feed flow rate (Qf ), and up-flow velocity (Vup ). The maximum hydrogen content, hydrogen production rate (HPR), hydrogen yield (HY), and COD removal were achieved at 55%, 4800 mL H2 /cycle, 321 mL H2 /g-COD, and 24.33%, respectively at Qf 8 L/cycle (HRT = cycle = 10.5 h) and Vup 2.0 m/h. The performance of the parameters from the optimum identified area was assessed at Qf 5.5 L/cycle (HRT = 15.3 h), and Vup 1.8 m/h, resulted in a maximum hydrogen content, HY, and HPR of 72%, 340 mL H2 /g-COD, and 5100 mL H2 /cycle, respectively. At optimum conditions, Clostridium sensu stricto 1 was found to be the dominant hydrogen-producing bacteria in the system. The results of this study may provide a practical basis for developing a UASFF reactor prototype based on empirical data. Graphical abstract: Image 1 Highlights: Dark fermentative hydrogen production from palm oil mill effluent. Optimization of up-flow velocity and feed flow rate in UASFF reactor. The optimum H2 production rate achieved was 5100 mL H2 /cycle at HRT 15.3 h, and OLR 23.54 g-COD/l.d. The bacterial community in H2 production sludge was dominated by Clostridium sensu stricto 1.